2019
DOI: 10.1016/j.matt.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation in Liquid Metal Nanoparticles

Abstract: Although various electronic, chemical, and biomedical applications have been demonstrated for nanoparticles made from gallium-based liquid metal alloys, fundamental physical properties such as phase behavior of such nanoparticles are still significantly underexplored. Here, Tang and coworkers present the in situ investigation of phase separation in binary and ternary spherical liquid metal nanoparticles upon cooling, and demonstrate the coexistence of solid core/liquid shell without the support of a crystallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 48 publications
4
99
0
Order By: Relevance
“…Such a phase separation enables alloy particles that have stronger heat conductivity over a broad range of temperature than other typical alloy particles. Tang et al reported phase separation of spherical Ga based nanoparticles formed solid‐core/liquid‐shell structure upon lowering temperature. They demonstrated the phase separation not only in binary nanoparticles but also in ternary nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Such a phase separation enables alloy particles that have stronger heat conductivity over a broad range of temperature than other typical alloy particles. Tang et al reported phase separation of spherical Ga based nanoparticles formed solid‐core/liquid‐shell structure upon lowering temperature. They demonstrated the phase separation not only in binary nanoparticles but also in ternary nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that in small droplets of liquid Ga, nanocrystal solid phases are always formed near the interfaces . Additionally, a conspicuous phase separation is seen in a reduction of temperature below the eutectic melting point in liquid metal droplets . Here, the dynamic of the system is more complicated, as the system is vigorously sonicated, and energy is constantly applied to it.…”
Section: Resultsmentioning
confidence: 99%
“…The study of optical properties of noble metal assisted-liquid metal nanoparticles will provide multifunctionality to plasmonic response of liquid metals and also makes them chemically stable to some extent which they lack off. The plasmonic response of some liquid metal alloys eutectic gallium indium (EGaIn) for the development of active devices to be functioned over wide region of electromagnetic spectrum has been reported [39,40]. Also, many experimental and theoretical studies have been carried out for synthesization of gallium-based alloys such as gallinstan but as per our knowledge, no study is reported for the plasmonic behavior of elemental liquid metals and their alloys.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al studied the phase behavior of gallium based liquid metal alloy (EGaIn) at micro-and nano-size scale [39].…”
Section: Research In Progressmentioning
confidence: 99%